2002
DOI: 10.1080/15287390252808055
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxic Effects of 2-Bromopropane in Male Sprague-Dawley Rats: A 28-Day Exposure Study

Abstract: Immunotoxic effects of 2-bromopropane were investigated in male Sprague-Dawley rats. The rats were treated orally daily with 2-bromopropane at 100, 330, or 1000 mg/kg for 28 consecutive days. Four days before necropsy, the rats were immunized intravenously with sheep red blood cells (SRBCs). The body and thymus weights were significantly reduced by treatment with 2-bromopropane at the highest dose. In addition, the numbers of splenic and thymic cells were decreased by 2-bromopropane. In hematology, the numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although sever al studies showed t hat phenol and 2-BP have a t oxic potent ial on t he immune syst em because t he number of whit e blood cells was significant ly decr eased when rats or wor ker s wer e exposed [25][26][27], litt le is known about the effects of phenol and 2-BP on cytokines product ion by mouse spleen cells. Here, we demonstr at e t hat phenol downregulates IL-1, IL-6 and TNF gene expression, and t hat 2-BP suppr esses TNF gene expr ession.…”
Section: Discussionmentioning
confidence: 99%
“…Although sever al studies showed t hat phenol and 2-BP have a t oxic potent ial on t he immune syst em because t he number of whit e blood cells was significant ly decr eased when rats or wor ker s wer e exposed [25][26][27], litt le is known about the effects of phenol and 2-BP on cytokines product ion by mouse spleen cells. Here, we demonstr at e t hat phenol downregulates IL-1, IL-6 and TNF gene expression, and t hat 2-BP suppr esses TNF gene expr ession.…”
Section: Discussionmentioning
confidence: 99%
“…Both processes were quantified subsequently in another study . Jeong et al (2002) found an overall decrease in immunological cells in the spleen and thymus as well as peripheral circulating blood cells after immunization with sheep blood cells, which was performed 4 days prior to killing, after a 28-day oral administration with 2-bromopropane at 100, 300 or 1,000 mg/kg/day. Although thymocytes seemed to be more sensitive (significant decrease, ‡330 mg/kg) to 2-bromopropane than splenocytes (1,000 mg/kg), the immunological suppression may be considered as a part of the overall reduction of bone marrow cells, which was observed in the initial studies (Ichihara et al 1996Nakajima et al 1997).…”
Section: Female Reproductive Toxicitymentioning
confidence: 99%